Relationship between serum total carbon dioxide concentration and bicarbonate concentration in patients undergoing hemodialysis - Hirai, Keiji (Kidney Res Clin Pract, 2020)
BACKGROUND: Few studies have investigated the relationship between serum total carbon dioxide (CO(2)) concentration and bicarbonate ion (HCO(3)(-)) concentration in patients undergoing hemodialysis. We determined the agreement and discrepancy between serum total CO(2) and HCO(3)(-) concentrations and the diagnostic accuracy of serum total CO(2) for the prediction of low (HCO(3)(-) < 24 mEq/L) and high (HCO(3)(-) ≥ 24 mEq/L) bicarbonate concentrations in hemodialysis patients. METHODS: One hundred forty-nine arteriovenous blood samples from 84 hemodialysis patients were studied. Multiple linear regression analysis was used to determine factors correlated with HCO(3)(-) concentration. Diagnostic accuracy of serum total CO(2) was evaluated using receiver operating characteristic curve analysis and a 2 × 2 table. Agreement between serum total CO(2) and HCO(3)(-) concentrations was assessed using Bland-Altman analysis. RESULTS: Serum total CO(2) concentration was closely correlated with HCO(3)(-) concentration (β = 0.858, P < 0.001). Area under the curve of serum total CO(2) for the identification of low and high bicarbonate concentrations was 0.989. Use of serum total CO(2) to predict low and high bicarbonate concentrations had a sensitivity of 100%, specificity of 50.0%, positive predictive value of 96.5%, negative predictive value of 100%, and accuracy of 96.6%. Bland-Altman analysis showed moderate agreement between serum total CO(2) and HCO(3)(-) concentrations. Discrepancies between HCO(3)(-) and serum total CO(2) concentrations (serum total CO(2) - HCO(3)(-) ≤ -1) were observed in 89 samples. CONCLUSION: Serum total CO(2) concentration is closely correlated with HCO(3)(-) concentration in hemodialysis patients. However, there is a non-negligible discrepancy between serum total CO(2) and HCO(3)(-) concentrations.